Planning as an element of strategic management in tourism - Ilić Biljana; Stefanović Vidoje (Trendovi u Poslovanju)
If management is understood as a process of making and sustaining the needed conditions where individuals, acting in organized groups, accomplish predicted goal, then the activities of management are very heterogeneous. They include different ways of showing, in the process of founding, current businesses and long-term (strategic) development of business systems in tourism. Because of that the planning should be made. The concept of planning in tourism is equally complex as the concept of tourism itself. The planning in tourism should be understood as a multiplex occurrence because the touristic complex is also multiplex. That's why the folowing question is important: what exactly should be planned in tourism, is it the whole phenomenon as such, its parts (economic and non-economic), special subjects which directly or indirectly take part in tourism, or planning touristic movements? Planning is one of the sub-processes of strategic management, and the Paper gives an insight into planning in tourism as an important factor of the economy, especialy on the ways of long-term planning.